STRATEGIC POLICY AS THE KEY CONTROL OF QUALITY MANAGEMENT OF SCHOOL LIBRARY INFORMATION SERVICES IN MANAGEMENT PERSPECTIVE - BAKHTIYAR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of this research is trying to describe the strategic policy implications of the management and development of school libraries. Research has an object of analysis accuracy, using the basis of a comprehensive detailed study, focusing on important content is the study of the implications of strategic policy in the management of school libraries. The research covered the basic analysis through focusing on studies on the application of library management that produces strategic policies in the management and development of school libraries. Research analysis, requires realistic critical thinking, applies a concept to the historical period, then it is appropriate to use a historical approach. characterized by highly dominating realistic critical inquiry for the development of a thought or term. Primary information sources are utilized as primary data. Collection of historical approach data, is to empower library research by reading a variety of literature, based on library management subject matter reading, strategic policy, library management and development. Qualitative descriptive analysis based on the source of analysis comes from a variety of theoretical, research and non-research material. Research predominates the description and evaluation of factual facts, in order to obtain solutions to the problematics contained in social phenomena. The validity of the research is realized through the implementation of in-depth analysis requires content analysis, to analyze the meaning of the main concepts namely the impact of library management on library management and development. Observation is empowered for the most important component to support the construction of theory. The result of the research is that strategic policy has a constructive positive impact in achieving the goals of the school library in accordance with the vision and mission of the school institution that houses it.